This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Solutions to Math 201 Final Exam from spring 2007 p. 1 of 16 (some of these problem solutions are out of order, in the interest of saving paper) 1. given equation: 1 2 ( x 1) 1 3 x = 4 both sides 6: 6 1 2 ( x 1) 6 1 3 x = 6 4 multiply numbers to cancel denominators: 3( x 1) 2 x = 24 distribute: 3 x 3 2 x = 24 combine like terms: x 3 = 24 both sides +3: x = 27 . 2. given equation: x 2 = 7 x 5 2 both sides 2x: 2 x x 2 = 2 x 7 x 2 x 5 2 cancel denominators: 6 2 x x 6 2 = 2 6 x 7 6 x6 2 x 5 6 2 clean up: x 2 = 14 5 x both sides 14 and +5 x : x 2 + 5 x 14 = 0 factor: ( x + 7)( x 2) = 0 answers: x = 7 or x = 2. So the sum of the two answers is 7 + 2 = 5 . 3. Note that this equation can be written in the form 2 u 2 + 3 u = 2, where the u represents the quantity x 1 . This is sometimes called a quadratic form equation. The strategy for solving them is to solve the equation for u first, and then when the uvalues are known, solve for x from there: equation: 2 u 2 + 3 u = 2 both sides 2: 2 u 2 + 3 u 2 = 0 factor: (2 u 1)( u + 2) = 0 finish solving for u : 2 u 1 = 0 or u + 2 = 0 = u = 1 2 or u = 2. Replace u by x 1 : x 1 = 1 2 or x 1 = 2 rewrite negative exponent: 1 x = 1 2 or 1 x = 2 1 reciprocate (flip) both sides of each equation: x = 2 or x = 1 2 . Note: reciprocating both sides of an equation is only valid when you have (single fraction) = (single fraction). 4. This problem is just asking you to determine the smallest and largest allowable values that h can have, based on the given inequality. If we solve the inequality, the answers are revealed: inequality: 4 h 50 30 rewrite without the : 30 4 h 50 30 all sides + 50: 20 4 h 80 all sides 4: 5 h 20 . So minimum h value is 5 and maximum is 20 . 6. a) ( f + g )( x ) = f ( x ) + g ( x ) = x + 1 + x . b) ( fg )( x ) = f ( x ) g ( x ) = ( x + 1) p ( x ) . c) ( f g )( x ) = f ( g ( x )) = f ( x ) = x + 1 . d) ( g f )( x ) = g ( f ( x )) = g ( x + 1) = x + 1 . e) From part (d), ( g f )( x ) = x + 1 . The only restriction on x in this expression is caused by the squareroot. For a squareroot to be defined, the inside expression must be 0. So the domain here is x + 1 0, which is the same as x  1, which is written as the interval 1 , ) . 7. To find the formula for f 1 ( x ) when you are given the formula for f ( x ): 1) write the relation down with y as the output (rather than f ( x ), if the relation was given that way); 2) exchange x and y in the relation; 3) solve the new relation for y ; 4) replace y by f 1 ( x ). Here goes: original function: f ( x ) = 2 x 1 put in the y : y = 2 x 1 exchange x and y : x = 2 y 1 solve for y : both sides + 1: x + 1 = 2 y both sides 2: x + 1 2 = y replace y by f 1 ( x ): f 1 ( x ) = x + 1 2 . 5. This type of function is referred to in some texts as a casedefined function. The graph of such a function is madeThis type of function is referred to in some texts as a casedefined function....
View
Full
Document
 Spring '08
 SMITH
 Math

Click to edit the document details